2014
DOI: 10.1093/jxb/eru226
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of water-use efficiency and its relation to growth in maritime pine

Abstract: To meet the increasing demand of wood biomass worldwide in the context of climate change, developing improved forest tree varieties for high productivity in water-limited conditions is becoming a major issue. This involves breeding for genotypes combining high growth and moderate water loss and thus high water-use efficiency (WUE). The present work provides original data about the genetics of intrinsic WUE (the ratio between net CO2 assimilation rate and stomatal conductance, also estimated by carbon isotope c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 80 publications
8
55
2
1
Order By: Relevance
“…However, no clear trend in correlations based on within-species diversity between growth and d 13 C can be deduced from the literature on perennial species (Zhang et al, 1994;Nguyen-Queyrens et al, 1998;Johnsen et al, 1999;Prasolova et al, 2001;Brendel et al, 2002;Xu et al, 2003;Weih et al, 2006;Monclus et al, 2012). Similar to our study, either absent or positive correlations have been found in Pinus pinaster (Marguerit et al, 2014) and Castanea sativa (Casasoli et al, 2004). As already discussed by Brendel et al (2002), the relationship between growth and WUE depends theoretically on the relative influence of the variability in New Phytologist photosynthesis (independent of stomatal limitations) compared with the variability in stomatal conductance.…”
Section: The Relationship Between D 13 C and Growth In A Breeding Persupporting
confidence: 62%
See 1 more Smart Citation
“…However, no clear trend in correlations based on within-species diversity between growth and d 13 C can be deduced from the literature on perennial species (Zhang et al, 1994;Nguyen-Queyrens et al, 1998;Johnsen et al, 1999;Prasolova et al, 2001;Brendel et al, 2002;Xu et al, 2003;Weih et al, 2006;Monclus et al, 2012). Similar to our study, either absent or positive correlations have been found in Pinus pinaster (Marguerit et al, 2014) and Castanea sativa (Casasoli et al, 2004). As already discussed by Brendel et al (2002), the relationship between growth and WUE depends theoretically on the relative influence of the variability in New Phytologist photosynthesis (independent of stomatal limitations) compared with the variability in stomatal conductance.…”
Section: The Relationship Between D 13 C and Growth In A Breeding Persupporting
confidence: 62%
“…(Marguerit et al, 2012)). Stable genomic regions for d 13 C have been detected across environments in Oryza sativa (Laza et al, 2006), Triticum aestivum (Rebetzke et al, 2008), Quercus robur (Brendel et al, 2008) and Pinus pinaster (Marguerit et al, 2014), which suggests low genotype-by-environment interaction (G 9 E). Together with genome sequencing, quantitative trait locus (QTL) studies open up new opportunities to characterize the molecular factors underlying d 13 C variation and, indirectly, WUE.…”
Section: Introductionmentioning
confidence: 99%
“…Existing forest tree breeding programmes mostly rely on improving wood traits favourable for timber and pulp as well as disease and pest resistance (reviewed by Mullin et al, , for conifers). However, adaptation to a changing climate is generally considered indirectly by evaluating growth or survival (Marguerit et al, ). Given the predicted increase in drought frequency and severity, the importance of plantation forestry on the hydrological cycle, and the increasing demand for water from rural and urban sectors, the issue of water use by forests will likely be one of the most important questions in many countries in the coming decades (Dunningham, Kirschbaum, Payn, & Meason, ; Dvorak, ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the experimental design used here (sample size of less than 500 genotypes and no clonal replicates) only strong QTL effects would be detectable. In maritime pine, QTL mapping, based on two- or three-generation pedigrees, has been carried out for height and radial growth [63], water-use efficiency [64, 65], wood properties [35], and traits relating to photosynthesis [66], but no previous study has addressed the genetic architecture of stem straightness. To the best of our knowledge, only one study in a P .…”
Section: Discussionmentioning
confidence: 99%